Financial Inclusion and Inclusive Growth : A Review of Recent Empirical Evidence - Demirguc-Kunt, Asli; Klapper, Leora; Singer, Dorothe (World Bank, Washington, DC, 2017)
There is growing evidence that appropriate financial services have substantial benefits for consumers, especially women and poor adults. This paper provides an overview of financial inclusion around the world and reviews the recent empirical evidence on how the use of financial products -- such as payments services, savings accounts, loans, and insurance -- can contribute to inclusive growth and economic development. This paper also discusses some of the challenges to achieving greater financial inclusion and directions for future research.